Prevalence of Anterior Dental Trauma and Its Associated Factors among Preschool Children Aged 3-5 Years in Khartoum City, Sudan - Alaa Gamaleldin Sulieman; Elhadi Mohieldin Awooda (Hindawi Limited, 2018)
Background. Traumatic dental injury (TDI) is a challenging public health problem. Its incidence and prevalence vary within countries, states, and different social groups. Aim. The purpose of this study was to determine the prevalence of traumatic dental injuries in primary incisors among 3-5-year-old Sudanese preschool children and associated factors such as age, sex, and size of overjet and anterior open bite. Materials and Methods. Descriptive cross-sectional study was carried out among 600 preschool children (3-5 years old) selected by multistage cluster technique from preschools located in Khartoum city, Sudan. The data regarding age, sex, causes, and treatment of TDI were collected from the mothers through structured interview questionnaire. Children were examined in an upright position, using mouth mirror and torch. A single examiner assessed the type of trauma, the tooth involved, and overbite/overjet. The data were analyzed statistically through descriptive analysis, and the chi-square test was used to compare between different variables with P<0.05. Results. The prevalence of traumatic dental injuries (TDIs) was 18.5%. Enamel fractures were the most common type (74.8%), followed by enamel and dentin (11.7%). The maxillary central incisors were the most commonly affected teeth, and the home was most common place for TDI. The prevalence rate was 45% in boys and 55% in girls with a statistically significant difference (P=0.02). Conclusions. The prevalence of traumatic dental injuries to the primary anterior teeth among the Sudanese preschool children was relatively high (18.5%). Factors such as overjet size, overbite size, and lip competency were not significantly correlated with dental trauma among the studied population.